Genetic polymorphisms and organophosphate neurotoxicity amongst emerging farmers in the Western Cape - Glass, Tracy (Centre for Infectious Disease Epidemiology and Research (CIDER), 2017)
BACKGROUND: Long-term exposure to organophosphates (OPs) can cause chronic neurotoxic effects which may be modulated by genetic polymorphisms of xenobiotic metabolising enzymes (XMEs). No previous study investigated XME modulation of neurotoxicity outcomes. OBJECTIVES: To investigate whether XMEs polymorphisms modulate OP neurotoxicity among emerging farmers. METHODS: A cross-sectional study of 301 emerging farmers was conducted in the rural Western Cape of South Africa. Neurotoxicity testing included the World Health Organisation Core Test Battery (digit span forward and backward) and vibration sensitivity testing. Questionnaire items included demographic data, potential confounders and work history of pesticide exposures. Blood samples were analysed for genetic polymorphisms of the following XMEs; glutathione S-transferases (GST), N-acetyltransferases (NAT) and Paraoxonase (PON1). RESULTS: Median age was 39 (30-48) and most had 9 years of education or less (65.5%). 54% of the participants were OP pesticide applicators. There was a low prevalence of the GST null genotype (GSTT-1% and GSTM-16%) and the GA and GG genotype for NAT (10%). Modulation of OP exposure and neurotoxic outcome relationships by NAT, PON1 at position 192 and GST was indicated in multivariate analysis. The strongest evidence of modification was by NAT on the relationship between pesticide poisoning and impaired vibration sense. Poisoned individuals with the GG genotype were more likely to suffer from impaired vibration sense compared to GA and AA genotypes. CONCLUSION: Genetic polymorphisms of NAT, PON1 (at position 192) and GSTM may modify the relationship between OP exposure and neurotoxicity. Larger longitudinal studies are required to determine whether preventive strategies can be developed to improve health amongst the identified vulnerable groups.